PENGARUH PENGGUNAAN MULTIMEDIA SMART TV TERHADAP KEAKTIFAN BELAJAR SOSIOLOGI SISWA SMA NEGERI 3 BULUKUMBA - Torro, Supriadi; Irwansyah, Idham; Aini, Syarifah (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2023)
The purpose of this study is to find out: 1) Overview of smart TV multimedia learning media in the field of sociology studies at UPT SMA Negeri 3 Bulukumba. 2) Overview of student learning activity in the field of sociology at UPT SMA Negeri 3 Bulukumba. 3) The influence of the use of smart TV multimedia media on student learning activity in the field of sociology studies at UPT SMA Negeri 3 Bulukumba. This study used a type of quantitative research with a descriptive approach, the total population in this study was 126 people. The process of determining the sample size using propability sampling techniques, namely proportionate stratified random sampling which is determined through the Slovin formula and obtained a sample number of 97 people. Data collection techniques in the form of questionnaires and documentation. Validity test using Bivariate Person correlation technique and reliability test using Alpha Cronbach. Data analysis techniques use descriptive statistics and inferential statistical analysis through the help of IBM SPSS Statistics application version 25 for Windows.The results of this study show that: 1) The description of multimedia smart TV learning media in the field of sociology studies at UPT SMA Negeri 3 Bulukumba is in the "high" category which shows the average score value (mean) of multimedia smart TV variables of 76.51 whose percentage rate is 76.50%. 2) The description of student learning activity in the field of sociology at UPT SMA Negeri 3 Bulukumba occupies the "high" category which shows the average value of student learning activity variables is 97.40 with a percentage rate of 77.92%. 3) There is an influence between multimedia variables smart TV on variables of student learning activity at UPT SMA Negeri 3 Bulukumba. This statement is evidenced from the significance value of 0.000<0.05 and the calculated value of 12.146 > t table 1.66071, so that the acquisition shows that variable X has an effect on variable Y. Then to find out the magnitude of the influence value between the two variables can be obtained from the R Square value of 0.608 which means that the multimedia smart TV variable (X) affects student learning activity (Y) simultaneously by 60.8% and the remaining 39.2% is influenced by other factors Outside of research.